Wild potato genetic reserves in protected areas: prospection notes from Los Cardones National Park, Salta, Argentina - Kozub, Perla Carolina; Ibañez, Verónica Noé; Digilio, Ariana; Atencio, Hugo Marcelo; Garavano, María Eugenia; Sánchez, María Elena; Marfil, Carlos Federico (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2022)
Wild potato species (WPS) are vital genetic resources to improve the productivity and sustainability of the third most important food crop worldwide. Although in situ conservation of this germplasm has been considered the most appropriate strategy, establishment of Genetic Reserves is still incipient. Northwest Argentina is among the priority regions for establishing WPS Genetic Reserves, whose designation within Protected Areas is accepted as the most efficient approach. In this work, we present results of the prospection and collection of WPS in Los Cardones National Park, a Protected Area with high environmental heterogeneity and diversity of plant communities. Four wild and one cultivated potato species were identified in different physiognomic vegetation units: Solanum acaule, S. brevicaule, S. boliviense, S. vernei and S. tuberosum group Andigenum. In the four WPS, characters of interest for plant breeding have been described. Through the development of environmental education workshops and the monitoring over two consecutive years within a worldwide priority site, we have established a baseline on which in situ conservation will be projected to preserve an essential component of the natural and cultural America's patrimony.